Parental Involvement and Chabacano Language Proficiency among High School Students in Ternate, Cavite - Astorga, John Mark; Lorio, Jenalyn S.; Asaula, Johnder S.; De Luna, Charlyn O.; Sean, Lagulao; De Leon, Arianne (Future Science / FSH-PH Publications, 2025)
This study examined the connection between parental involvement and Chabacano language ability among Chabacano-speaking students from Ternate, Cavite. Chabacano in Ternate is based on an Indonesian-Malay ancestry but it evolved into a creole language based on the Spanish colonial period. Today, Chabacano in Ternate is still endangered. A descriptive-correlation research design was employed to examine the relationship between parental involvement and Chabacano language ability. Data were collected through a survey questionnaire using purposive sampling which gathered 138 high school students, The study found that the students with more parental support such as support for use of the language at home and support for community-based learning programs had a greater overall ability in Chabacano. The study reveals strong and statistically significant correlations between parental involvement and all domains of Chabacano proficiency. The highest correlation was found in conversational skills (r = 0.584), followed closely by overall proficiency (r = 0.591), indicating that students who receive consistent support from their parents tend to perform better in using the language interactively. Additionally, some differences in demographic means demonstrated differences in proficiency levels. Overall, the study highlights the important role of family involvement in the preservation of minority languages such as Chabacano, especially in an increasingly assimilated community where family involvement can demonstrate an appreciation of the cultural and unique tradition that exists. It was concluded that a greater involvement by parents can reverse a decline in the Chabacano language, and the next generation in Ternate, ...